Application of Mahfudzat Method: Field Research, Test Results of Teaching Learning Process at MAN Model Bojonegoro - Hanik Fauziyah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
This action research is intended to improve learning outcomes by memorization or mahfudzat. It aims specifically at describing the ability of teachers in managing learning with mahfudzat method on Geography of class X IPS Unggulan 2 MAN 1 Model Bojonegoro, academic year of 2016/2017. This research is a classroom action research, because it comes from the problems of teachers who teach in the classroom and take action to overcome the problems in the classroom, with the type of quantitative methods. The results of this research reveal that the ability of teachers in managing learning by applying the method of mahfudzat in the lesson of Geography can improve the learning outcomes of the students of class X IPS Unggulan 2 MAN 1 Model Bojonegoro academic year 2016/2017.